A Study in the Political Transformation of Ughoton, (Old Seaport of Benin Kingdom), 1440-1897 - Ediagbonya Michael; Buhari Lateef Oluwafemi (Polit Journal Scientific Journal of Politics, 2023)
This paper examines the political transformation of Ughoton between the period of 1440-1897. The political system before 1440 in the community also came to focus. The political institutions which witnessed transformation include the appointment of Ohen-Okun of Ughoton as the first Benin ambassador to Portugal and it was compulsory for the heir-apparent to the Benin throne to be initiated into edion-age grade. Again the age grades which include ‘Iroghae’ the ‘Ighele’ and the edion witnessed transformation between 1440-1897. The researcher obtains data from primary and secondary sources. Oral interviews serve as primary sources. Books, journals, articles, newspapers, projects, theses, dissertations and intelligence reports serve as secondary sources. It was found that the Ohen-Okun of Ughoton became the first Benin Ambassador to the outside world. It was also demonstrated that the heir-apparent to the Benin throne must be initiated into ‘edion age grade in Ughoton before he can be crown as Oba of Benin. It was also found that the age grade system in Ughoton went through serious transformation. In conclusion, the visit of Ohen-Okun of Ughoton to Portugal attracted many foreigners like Christian Missionaries, Chroniclers, Scholars, visitors and traders to Ughoton.